A Study of Digital Payments : Trends, Challenges and Implementation in Indian Banking System - Bhasin, Narinder Kumar and Rajesh, Anupama (International Journal of Virtual Communities and Social Networking, 2018)
The challenges and emergence of a global economy and a Digital First World has created financial disruptions in e-commerce and e-business around the globe. The collaborations of banks with Fintech companies have led to digitalization being an important component of their business and marketing strategy. The application of e-banking has been demonstrated as an effective cost reduction, risk management and provides quick services to the customers. Nowadays, e-banking services have already ensured opportunities to reduce expenditures on physical structures. However, in some previous studies it has been showed that e-banking has helped banks and financial institutions to reduce costs, increase revenue, and increase customer experience. With the growth of digital banking in India, it is significant to analyze the actual situation of customer satisfaction in the banking sector. This article evaluates the various new digital banking technologies in the banking sector of India which have gained momentum after various banking reforms like the digital financial inclusion, demonetization and GST implementation. It also identifies the relationship between the increasing trends in the usage of electronic banking and a customer paradigm shift from traditional cash and paper-based cheque payment systems and evaluates various challenges and opportunities in the implementation of digitalization. This research was carried out using multiple methodologies.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9panZjc24uMjAxODAxMDEwNA